A Nitric Oxide-Releasing Heparin Conjugate for Delivery of a Combined Antiplatelet/Anticoagulant Agent - Suchyta, Dakota J. (American Chemical Society, 2014)
[Image: see text] Heparin is a widely used anticoagulant due to its ability to inhibit key components in the coagulation cascade such as Factor Xa and thrombin (Factor IIa). Its potential to preferentially bind to antithrombin (ATIII) results in a conformational change and activation that leads to the prevention of fibrin formation from fibrinogen and ultimately obstructs a hemostatic plug from forming. Nitric oxide (NO) exhibits potent antiplatelet activity attributed to its capacity to increase the amount of cyclic guanosine monophosphate (cGMP) within platelets, which decreases the Ca(2+) concentration required for platelet activation. Currently there is no single agent that combines the functions of both antiplatelet and anticoagulant (anti-Xa and anti-IIa) activities to effectively block both the extrinsic and the intrinsic coagulation pathways. The research reported herein demonstrates the ability to combine the physiological capabilities of both heparin and NO into one functional compound via use of a spermine derivative of heparin, thus enabling formation of a novel diazeniumdiolate (NONOate). The heparin–spermine NONOate has a half-life of 85 min at 25 °C (pH 7.4). The heparin backbone of the conjugate maintains its anticoagulant activity as demonstrated via an anti-Xa assay, providing an anticoagulant conversion of 3.6 μg/mL of the heparin–spermine–NONO conjugate being equivalent to 2.5 μg/mL (0.50 IU/mL) of underivatized heparin in terms of anti-Xa activity. Using standard platelet aggregometry, it is shown that the functionality of the NO release portion of the heparin conjugate prevents (nearly 100%) platelet aggregation in the presence of adenosine diphosphate (ADP, platelet agonist).